A method of thermal and chemical activation of waste bleaching earth for preparation of a low-cost carbon-mineral adsorbent for chromium(VI) removal. Issue 8 (24th May 2018) - Polowczyk, I.; Cyganowski, P.; Lorenc-Grabowska, E.; Sawicki, R.; Bastrzyk, A.
ABSTRACT: In this study, the use of a spent bleaching earth for removal of Cr(VI) ions from aqueous solutions was investigated. The waste material derived from the process of vegetable oil purification was subjected to thermal and chemical activation. The so-prepared carbon-mineral adsorbents were characterised by the uptake of chromium(VI) from synthetic solutions. The highest adsorption capacities were obtained for adsorbents carbonised at 400°C (15.9 mg∙g −1 ) and activated with H2 SO4 (15.8 mg∙g −1 ). Based on the equilibrium and kinetic studies, it was concluded that the adsorption mechanism was based on chemisorption only since no correlation with the porous texture was found.